A comparison of common and new methods to determine martensite start temperature using a dilatometer. (2nd January 2017) - Kamyabi-Gol, A.; Herath, D.; Mendez, P. F.
ABSTRACT: This paper analyses the start of the martensitic transformation in 4140 steel from the point of view of six definitions, and discusses in detail the implications based on the better understanding of progression of the transformation. The application of two relatively new techniques (cooling curve analysis-CCA and dilation curve analysis-DCA) is among the methods studied. These new techniques allow for a more rigorous quantification of microstructural constituents at each step of the transformation. Experiments consisted of dilatometric analysis of 12 samples of 4140 steel with prior austenite grain sizes from 16 to 44 µm that were rapidly quenched in the dilatometer to form martensite. The results indicate that DCA and CCA are superior to traditional methods used to determine the martensite start temperature. The practical choice of 10% martensite fraction in CCA and DCA yielded Ms values statistically undistinguishable from ASTM A1033 or the tangent method. The practical choice of 1% martensite fraction in CCA and DCA yielded Ms values comparable to the offset method. The important implication of this finding is that Ms values determined with empirical methods should not be confused with the temperature of first appearance of martensite; instead, they correspond to martensite fractions of the order of 10%.